Edwardsiella tarda Tunes Tricarboxylic Acid Cycle to Evade Complement-Mediated Killing - Cheng, Zhi-xue; Gong, Qi-yang; Wang, Zhe; Chen, Zhuang-gui; Ye, Jin-zhou; Li, Jun; Wang, Jie; Yang, Man-jun; Ling, Xiao-peng; Peng, Bo (Frontiers in Immunology, 2017)
Evasion of complement-mediated killing is a common phenotype for many different types of pathogens, but the mechanism is still poorly understood. Most of the clinic isolates of Edwardsiella tarda, an important pathogen infecting both of human and fish, are commonly found serum-resistant. To explore the potential mechanisms, we applied GC-MS based metabolomics approaches to profile the metabolomes of E. tarda EIB202 in the presence or absence of serum stress. We found that TCA cycle was greatly enhanced in the presence of serum. The QRT-PCR and enzyme activity assays validated this result. Furthermore, exogenous succinate that promoting TCA cycle increased serum resistance, while TCA cycle inhibitors (bromopyruvate and propanedioic acid) that inhibit TCA cycle, attenuated serum resistance. Moreover, the enhanced TCA cycle increased membrane potential, thus decreased the formation of membrane attack complex at cell surface, resulting serum resistance. These evidences suggested a previously unknown membrane potential-dependent mechanism of serum resistance. Therefore, our findings reveal that pathogen mounts a metabolic trick, to cope with the serum complement-mediated killing.